L’art du Halqa entre réalité et fiction chez Tahar Ben Jelloun - TOURCHLI, Abderrahim (Studia Universitatis Babeș-Bolyai Dramatica, 2017)
The Art of Halqa Between Reality and Fiction in Tahar Ben Jellou’s Works. The tale occupies a place of choice in the stories of Tahar Ben Jelloun. It embraces the form of the narrative and takes its place. Thus it reinforces the fact a narrative can be narrated in a thousand ways. A polymorphic narrative that denies the linearity of classical narration. So, the use of the tale as a garant of the narrative at Ben Jelloun appeals to the Halqa as an art of the spectacle often practiced in public places, which belongs to orality and ancestral tradition: the storytellers of the public square Jamaà El Fna strive to tell the story of Ahmed-Zahra and often enter into dialogue and interaction with the audience. Thus, how is the staging of the narrative act and the communicative dimension of the narrative thanks to the convocation of the figure of the storyteller and the art of the Halqa? How is the emphasis on the dialectic of the real and of the imaginary, of the oral and written to criticize and unveil the social simulacrum?